1996
DOI: 10.1073/pnas.93.23.12759
|View full text |Cite
|
Sign up to set email alerts
|

Conformational influences of glycosylation of a peptide: A possible model for the effect of glycosylation on the rate of protein folding

Abstract: Improved strategies for synthesis make it possible to expand the range of glycopeptides available for detailed conformational studies. The glycopeptide 1 was synthesized using a new solid phase synthesis of carbohydrates and a convergent coupling to peptide followed by deprotection. Its conformational properties were subjected to NMR analysis and compared with a control peptide 2 prepared by conventional solid phase methods. Whereas peptide 2 fails to manifest any appreciable secondary structure, the glycopept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
82
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 23 publications
6
82
0
Order By: Relevance
“…This observation substantiates the general importance of this residue to structural integrity, even though it is not always necessary to preserve a folded structure, as it is for hCD2ad (17,19). Furthermore, the proximal N-linked GlcNAc of model synthetic N-linked glycopeptides is the most influential for rigidifying and biasing conformational space, including promoting ␤-turn and disulfide bond formation (5,8,(28)(29)(30), consistent with GlcNAc a playing a general kinetic role in glycoprotein folding.…”
Section: Discussionmentioning
confidence: 98%
“…This observation substantiates the general importance of this residue to structural integrity, even though it is not always necessary to preserve a folded structure, as it is for hCD2ad (17,19). Furthermore, the proximal N-linked GlcNAc of model synthetic N-linked glycopeptides is the most influential for rigidifying and biasing conformational space, including promoting ␤-turn and disulfide bond formation (5,8,(28)(29)(30), consistent with GlcNAc a playing a general kinetic role in glycoprotein folding.…”
Section: Discussionmentioning
confidence: 98%
“…However, in our model, we found that exogenous heparin had no effect on shedding, suggesting that it is unlikely that syndecans are binding to MMPs and directly inhibiting their activity. Another possible mechanism could be related to a change in protein folding and stabilization, which can be altered by changes in glycosylation (30,40). Removal of heparan sulfate could alter syndecan-1 core protein conformation and expose cryptic sites that are susceptible to protease cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence showing that a reducing environment can promote the generation of PrP Sc -like species (6,(16)(17)(18) suggests that factors affecting the stability of the disulfide bridge could also have an effect in preventing or promoting the PrP C to PrP Sc transition. Previous glycopeptide studies reveal that N-linked glycosylation can impact the conformation of protein fragments (28)(29)(30). In particular, we have shown that glycosylation can alter the thermodynamics of disulfide bond formation, favoring the oxidized form (31).…”
mentioning
confidence: 99%